Lanolin-based dexpanthenol cream, topical hydrocortisone or observation in the prevention of capecitabine-induced hand-foot syndrome: a phase III trial - Cintia Sayuri Kurokawa La-Scala; Artur Malzyner; Carmen Silvia Passos Lima; Daniela Dornelles Rosa; Fabio André Franke; Fernanda Maris Peria; Giuliano Santos Borges; Gustavo Colagiovanni Girotto; Leandro Brust; Magda Conceição Barbosa Gomes; Nilciza Maria de Carvalho Tavares Calux; Roberto Magnus Duarte Sales; et al. (Brazilian Journal of Oncology)
Introduction: The use of capecitabine is associated with hand-foot syndrome (HFS). Since there is anecdotal evidence that lanolin-based creams and topical steroids are useful for the treatment of HFS, we conducted a three- arm phase III trial to compare observation, lanolin-based cream with dexpanthenol (L-D), and topical hydrocortisone in the prevention of HFS. Material and Methods: Patients with breast or colorectal cancer with indication to use capecitabine as a single agent or in combination were randomized in an open-label fashion to one of the three arms. The initial capecitabine dose was 1,000 or 1,250mg/m2, according to the physicians discretion and clinical practice, and dose adjustments followed the local label. The primary endpoint was the frequency of HFS of any grade in the intent-to-treat population, whereas quality of life (QoL), change from baseline in performance status and adverse events were secondary endpoints. Results: Mean age among the 595 patients randomized was 58 years, and 69% were women. 37% of patients had advanced breast cancer and 63% of patients had colorectal cancer. Capecitabine was used as a single agent in 67% of patients; among the remaining 33% of patients, 82% were treated with oxaliplatin-based combinations. HFS of any grade was seen in 35.6% of patients in the observation group, 24.9% with L-D, and 34.3% with hydrocortisone (p=0.039). The unadjusted odds ratio for the frequency of HFS in the arm treated with L-D was 0.60 (95%CI, 0.39 to 0.92). Only between 2.6% and 9.4% of patients had grade 3 HFS. There were no statistically significant differences in mean change from baseline in any of the QoL scores, the distribution of performance status, or the frequency of adverse events among the three arms. Conclusion: L-D could be considered a standard strategy in the attempt to prevent capecitabine-induced HFS.